Bimbingan Penyuluhan Agama Terhadap Muallaf Perempuan - Eva putri Saragi; Waizul Qarni (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to provide counseling guidance to converts who experience difficulties in knowing and studying the Islamic religion, especially to deepen the jurisprudence of worship and Islamic aqidah so that female converts in Hutatoruan VII Village can perform their prayers properly and strengthen their faith given by extension workers from the Ministry office. The religion of Islam in North Tapanuli Regency. The research method applied to this research is qualitative research with case studies in which researchers carefully investigate an event, activity, process, and interviews related to research and observation by collecting field data it is found that the number of converts in Hutatoruan VII Village is 80. 60 people who were active in extension guidance held by extension workers. The results of this study indicate that the existence of religious counseling guidance for female converts in the village of Hutatoruan VII is very effective and has an impact on overcoming the problems and difficulties of converts in learning and getting to know Islam.